The Tausug parang Sabil Kissa as literary, cultural, and historical materials - Asain, Calbi A. (2006)
The parang sabil kissa, interchangeably referred to as ballads as well as epics, depending on their seriousness and length, are quite familiar to the Tausugs, the natives of the Sulu Province. They are sung in order to perform a twofold function ? to entertain and instruct. The singers of this oral tradition may be male or female, and most of the can be found in mainland Jolo. As literary materials, the parang sabil kissa are in verse whose lines rhyme, and the language used, which is Tausug or Bahasa Sug, has special intensity. These kissa are usually composed of several stanzas. When they are sung, the singer, usually a female, also plays the Tausug gabbang or native bamboo xylophone, accompanied with the biyula or native violin played by a male companion. As cultural materials, the parang sabil kissa reflect the life ways of the people, especially their values. Since they are handed down from one generation to the next, they can be considered as carriers of the Tausugs? cultural heritage, which is the source of the people?s ethnic or cultural identity. Moreover, they do not only mirror the people?s customs across generations; they also preserve these in the process. As historical materials, the parang sabil kissa narrate the Tausugs? historical experience and circumstances, especially the people?s resistance to the incursion of foreign invaders and their subsequent retaliatory actions and decisions in order to defend their freedom, homeland, and way of life. In contemporary history, some parang sabil kissa narrate the fate of the revolutionary movements and their leaders. This paper discusses the potentials and contributions of the parang sabil kissa to the study of the Tausug literature, culture, and history as part and parcel of the Filipino Muslim community and the Filipino nation as a whole.
Includes bibliographical references (pages 279-281).